Experimental Study on the Effect of Zigzag Configuration of Paraffin Wax-Filled Aluminum Containers on the Thermal Performance of a Photovoltaic Thermal System - Sugito Julio Putra; Ayu Zahra Chandrasari; Ahmad Rajani (TALENTA Publisher, Universitas Sumatera Utara, 2026)
The performance of photovoltaic (PV) panels decreases significantly as operating temperatures rise. To mitigate this, forced-air cooling is often employed, but fluctuating outdoor solar radiation makes the integration of phase change materials (PCM) essential for effective heat regulation. This study experimentally evaluates the thermal performance of an air-based photovoltaic thermal (PV/T) system integrated with a zigzag arrangement of aluminum containers filled with paraffin wax PCM. The zigzag geometry was specifically designed to extend the contact path for forced convective heat transfer. Three PCM mass variations (150 g, 200 g, and 250 g) were tested outdoors in an urban environment from 09:00 to 15:00 WIB. The system's thermal response was monitored using K-type thermocouples, DHT22 sensors, and a solar power meter to record radiation intensity, component temperatures, and inlet-outlet air temperature differences (ΔT). Experimental results showed average solar irradiance values of 817.16, 643.76, and 606.05 W/m² for the 150 g, 200 g, and 250 g tests, respectively. The PV backsheet recorded the highest average temperatures across all setups, reaching up to 57.88°C. Notably, the 200 g PCM configuration demonstrated the optimal thermal response, achieving the highest peak PCM ΔT of 10.98°C at 13:00. Furthermore, the system yielded average positive air ΔT values of 6.37°C, 5.00°C, and 4.83°C for the respective masses. These findings confirm that forced air flow effectively removes heat from the zigzag PCM section, highlighting that selecting an appropriate PCM mass is critical for balancing heat absorption and continuous convective removal under dynamic field conditions.